Episternus onthophagi: a new monotypic genus of epizoic fungus found on Onthophagus beetles (Scarabaeoidea) - Górz, Andrzej; Boroń, Piotr (Phytotaxa, 2018)
During research on the biological diversity of coprophagous Scarabaeoidea in the Polish Carpathians, a particular morphotype of epizoic fungus was found on several species of coprophages of the Onthophagus genus. The fungus occurs on the mesosternum and legs of the beetles. Detailed morphological observations and genetic analyses proved this epizoic fungus to be distinct from any other known species, it is new to science. It is very characteristic in terms of morphological features, as it grows in the form of thallus closely adhered to the insect exoskeleton with only the outermost layer of cells viable. The shape of thallus itself is determined by its location on insect’s body. Only vegetative structures and conidial reproduction were observed. In the presented study, we describe and establish this newly found morphotype in the rank of new monotypic genus and document its distinctness with eleven barcode sequences. Three gene based, LSU plus SSU plus ITS, phylogenetic positioning places the new genus firmly nested within Lasiosphaeriaceae (Sordariales) with Zygospermella insignis (Mouton) Cain as its closest relative. No epizoic colonization of dung beetles was described in Lasiosphaeriaceae to date nor Lasiosphaeriaceae species with similar morphology. The potential role of the described epizoic fungus in the living environment of the Onthophagus dung beetles is discussed.